Immediate Reconstruction of Amputated Ear With Fascia Flap. Issue 1 (January 2020) - Kim, Beom-Jun; You, Jae-Pil; Jung, Jae-A; You, Hi-Jin; Kim, Deok-Woo
Abstract : Background: Various surgical methods have been used for reconstruction of an amputated ear, including microsurgical replantation and delayed reconstruction using synthetic material or autologous rib cartilage. The authors share our experience of immediate reconstruction using amputated cartilage and discuss the advantages compared to other techniques of reconstruction. Materials and Methods: The authors retrospectively reviewed the medical records of 3 patients who underwent immediate reconstruction of amputated ear by a single operator. In the cases, the amputees were washed; the skin and cartilage were separated. The ear cartilage was fixed to its original position with non-absorbable suture. Regional fascia flap was elevated and covered the ear cartilage. The amputee skin was redraped to cover the fascia flap. Several months after the operation, photographic assessment was done. Results: All 3 cases showed well-defined convolution, tolerable skin color, and patient satisfaction without any major complications. A patient showed mild temporal incision site alopecia. Conclusion: The above immediate reconstruction method can achieve reliable and favorable result with minimal complications. Abstract : Supplemental Digital Content is available in the text